REALIZATION OF THE RIGHT TO HEALTH OF THE PRISON POPULATION IN THE KYRGYZ REPUBLIC IN THE CONTEXT OF A PANDEMIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents the results of monitoring and assessing the state of prison health care during the COVID-19 pandemic in order to prevent the decline of COVID-19 cases. The monitoring was carried out in penitentiary institutions (IVS, pre-trial detention center, correctional colony and educational colony for male minors). The monitoring and evaluation methodology was based on interviewing persons held in these institutions and interviewing representatives of these institutions.
Keywords: prisoners, medical care, incarceration, penitentiary system, conditions of detention, budgetary funds, healthcare, medical education, skill development, human resources, state supervision.